DOKTRIN MANUSIA DAN DOSA - Elsa Oktavia; Sarmauli (ADISAM PUBLISHER, 2024)
Doctrine of humanity and sin within the context of Christian theology. It explains the creation of humans in the image of God, the fall into sin, and the consequences for the relationship between humanity and God. Sin, as a violation of God's law, not only has spiritual repercussions by separating humans from God but also results in social consequences that damage interpersonal relationships. Furthermore, this paper emphasizes the importance of understanding original sin and personal sin, which underline the necessity of redemption through Jesus Christ. The role of Jesus in sin atonement is central to restoring the relationship between humanity and God. Through His sacrifice, believers are given hope to live in victory over sin and experience life transformation. This paper aims to provide a deeper understanding of human conditions, the impact of sin, and the need for God's grace